Treatment and Clinical Outcomes of Transcatheter Heart Valve Thrombosis. (April 2015) - Latib, Azeem; Naganuma, Toru; Abdel-Wahab, Mohamed; Danenberg, Haim; Cota, Linda; Barbanti, Marco; Baumgartner, Helmut; Finkelstein, Ariel; Legrand, Victor; de Lezo, José Suárez; Kefer, Joelle; Messika-Zeitoun, David; et al.
<x xml:space="preserve">Abstract</x> Background— Valve thrombosis has yet to be fully evaluated after transcatheter aortic valve implantation. This study aimed to report the prevalence, timing, and treatment of transcatheter heart valve (THV) thrombosis. Methods and Results— THV thrombosis was defined as follows (1) THV dysfunction secondary to thrombosis diagnosed based on response to anticoagulation therapy, imaging modality or histopathology findings, or (2) mobile mass detected on THV suspicious of thrombus, irrespective of dysfunction and in absence of infection. Between January 2008 and September 2013, 26 (0.61%) THV thromboses were reported out of 4266 patients undergoing transcatheter aortic valve implantation in 12 centers. Of the 26 cases detected, 20 were detected in the Edwards Sapien/Sapien XT cohort and 6 in the Medtronic CoreValve cohort. In patients diagnosed with THV thrombosis, the median time to THV thrombosis post–transcatheter aortic valve implantation was 181 days (interquartile range, 45–313). The most common clinical presentation was exertional dyspnea (n=17; 65%), whereas 8 (31%) patients had no worsening symptoms. Echocardiographic findings included a markedly elevated mean aortic valve pressure gradient (40.5±14.0 mm Hg), presence of thickened leaflets or thrombotic apposition of leaflets in 20 (77%) and a thrombotic mass on the leaflets in the remaining 6 (23%) patients. In 23 (88%) patients, anticoagulation resulted in a significant decrease of the aortic valve pressure gradient within 2 months. Conclusions— THV thrombosis is a rare phenomenon that was detected within the first 2 years after transcatheter aortic valve implantation and usually presented with dyspnea and increased gradients. Anticoagulation seems to have been effective and should be considered even in patients without visible thrombus on echocardiography.